ACEF score as a predictor of new-onset atrial fibrillation in patients with ST-elevation myocardial infarction: A retrospective cohort study - Evliya Akdeniz; Burak Hünük; Cennet Yıldız; Süleyman Deniz Abdullahoğlu; Merve Ortakaya; Dilay Karabulut; Fatma Nihan Turhan Çağlar; Ömer Kozan (PLoS ONE, 2025)
Background New-onset atrial fibrillation (NOAF) during acute ST-elevation myocardial infarction (STEMI) is common and linked to adverse outcomes. This study aimed to assess the predictive value of the age–creatinine–ejection fraction (ACEF) score for NOAF in STEMI patients. Methods We retrospectively analyzed 951 STEMI patients who underwent primary percutaneous coronary intervention (PCI) at out tertiary center between 2020 and 2023. Patients with prior atrial fibrillation (AF), AF on admission, cardiogenic shock, heart failure, significant valvular disease, or failed PCI were excluded. Clinical, laboratory, and echocardiographic data were collected, and ACEF scores were calculated. NOAF was defined as any AF episode during hospitalization in patients without prior AF. The optimal ACEF cutoff was determined using receiver operating characteristic (ROC) curve analysis (Youden’s index), and multivariate logistic regression identified independent predictors of NOAF. Results NOAF occurred in 63 patients (6.6%). These patients were older, more often female, and had lower systolic blood pressure, lower left ventricular ejection fraction, and higher C-reactive protein and creatinine levels (all p < 0.05). In-hospital major adverse cardiac events (MACE) and mortality were significantly higher in the NOAF group than patients in without NOAF group (22.2% vs. 6.2%, and 15.9% vs. 4.3%, respectively; p < 0.001). The ACEF score was significantly higher in patients with NOAF (1.73 ± 0.74 vs. 1.42 ± 0.64, p < 0.001). ROC analysis showed an area under curve (AUC) of 0.643 (95% CI: 0.571–0.715; p < 0.001). An ACEF score ≥1.32 predicted NOAF with 73% sensitivity and 55.6% specificity. In multivariate analysis, ACEF remained an independent predictor of NOAF (OR ~1.5, p = 0.02), but among its components, only age was independently associated with NOAF (OR ~1.03 per year, p = 0.01). Conclusions The ACEF score modestly predicts NOAF in STEMI patients, but its predictive power only incremental to age alone. Further studies are warranted for this field.